2011
DOI: 10.1029/2010wr009800
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization of process domains in headwater drainage basins of a glaciated foothills region with complex longitudinal profiles

Abstract: [1] Lithologic transitions and glaciations create complex longitudinal profiles that control contemporary erosion and deposition processes. In areas with these characteristics, traditional morphometric approaches for predicting process domains, such as area-slope plots, can be augmented by considering other predictors measured from high resolution lidar-derived digital elevation models (DEMs). Ordinal logistic regression was used to model the distribution of hillslope, swale, colluvial channel, and fluvial cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…where p is the probability of a response being in a given or higher level category. An extensive review of OLR can be found in McCullagh (1980). An example of OLR applied in a watershed context can be found in McCleary et al 2011.…”
Section: Ordinal Logistic Regressionmentioning
confidence: 99%
“…where p is the probability of a response being in a given or higher level category. An extensive review of OLR can be found in McCullagh (1980). An example of OLR applied in a watershed context can be found in McCleary et al 2011.…”
Section: Ordinal Logistic Regressionmentioning
confidence: 99%
“…The calculation of SL / k in this study was a modification by McCleary et al . () of the equation used by Pérez‐Peña et al . (): SL/k=Sxrlnxrhshrwhere h s is the river head elevation (m), h r is the reach mid‐point elevation (m), and x r is the distance from the stream source to the middle of the reach (m).…”
Section: Methodsmentioning
confidence: 99%
“…Fluvial systems in deglaciated basins are often still responding to inherited topography and sediments at post‐glacial timescales, creating knick‐points along channel profiles due to differential erosion. These channels tend not to conform to the typical ‘graded’ concave‐up profile (Collins & Montgomery, 2011; McCleary et al, 2011; Phillips & Desloges, 2014; Thayer et al, 2016). Rivers carving through diverse deglaciated surfaces may experience a disequilibrium between stream energy and bed clast size leading to downstream variations in morphology (Desloges et al, 2020; Phillips & Desloges, 2014, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%